2006
DOI: 10.1126/science.1128868
|View full text |Cite
|
Sign up to set email alerts
|

Extending Top-Down Mass Spectrometry to Proteins with Masses Greater Than 200 Kilodaltons

Abstract: For characterization of sequence and posttranslational modifications, molecular and fragment ion mass data from ionizing and dissociating a protein in the mass spectrometer are far more specific than are masses of peptides from the protein's digestion. We extend the approximately 500-residue, approximately 50-kilodalton (kD) dissociation limitation of this top-down methodology by using electrospray additives, heated vaporization, and separate noncovalent and covalent bond dissociation. This process can cleave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
344
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(350 citation statements)
references
References 27 publications
3
344
2
1
Order By: Relevance
“…For Ca(H 2 O) 4 ϩ , both levels of theory indicate that Ca ϩ is solvated by four water molecules in plane with the metal ion, although we found a D 2h symmetry to be slightly lower in energy than the C s -symmetry structure with distorted O-Ca-O bond angles identified previously. For Ca(H 2 O) 5 ϩ and Ca(H 2 O) 6 ϩ , our calculations indicate that all water molecules in the lowest-energy structure coordinate directly to the metal ion, whereas the previous calculations indicate that structures with four inner-shell water molecules are lowest in energy. Because Watanabe et al [67] reported relative free energies for structures, it is difficult to directly compare these results.…”
Section: Ecd Energetics For Small Ca(h 2 O) N 2ϩ Clusterscontrasting
confidence: 74%
See 3 more Smart Citations
“…For Ca(H 2 O) 4 ϩ , both levels of theory indicate that Ca ϩ is solvated by four water molecules in plane with the metal ion, although we found a D 2h symmetry to be slightly lower in energy than the C s -symmetry structure with distorted O-Ca-O bond angles identified previously. For Ca(H 2 O) 5 ϩ and Ca(H 2 O) 6 ϩ , our calculations indicate that all water molecules in the lowest-energy structure coordinate directly to the metal ion, whereas the previous calculations indicate that structures with four inner-shell water molecules are lowest in energy. Because Watanabe et al [67] reported relative free energies for structures, it is difficult to directly compare these results.…”
Section: Ecd Energetics For Small Ca(h 2 O) N 2ϩ Clusterscontrasting
confidence: 74%
“…Clemmer and coworkers elegantly demonstrated that combining on-line liquid chromatography (LC) with ion mobility spectrometry and MS can greatly improve separations without increasing analysis times over LC/MS alone [2][3][4]. In contrast, the "top-down" approach to protein characterization has the advantage that de novo sequencing, including the identification and structural localization of labile posttranslational modifications, can be done directly on protein mixtures without proteolysis [5,6]. This top-down approach has greatly benefited from the development of electron capture dissociation (ECD), a method pioneered by McLafferty and coworkers [6][7][8][9].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The top-down MS strategy allows analysis of intact proteins to obtain a comprehensive assessment and localization of post-translational modifications (PTMs) and point mutations with full sequence coverage and without a priori knowledge. [27][28][29][30][31][32][33][34][35][36][37] It starts with measuring molecular weights of intact proteins followed by fragmentation of the protein in the mass spectrometer with tandem mass spectrometry (MS/MS) such as electron capture dissociation (ECD) 38 to obtain sequence information. ECD has been demonstrated to be especially valuable for mapping phosphorylation sites, because it preserves the labile PTMs during MS/MS process.…”
Section: Introductionmentioning
confidence: 99%